Correlation between the hydration of acyl chains and phosphate groups in lipid bilayers: Effect of phase state, head group, chain length, double bonds and carbonyl groups - Rosa, Antonio Sebastián (2019)
This paper demonstrates by means of FTIR/ATR analysis that water molecules intercalate at different extents in the acyl chain region of lipid membranes in correlation with the hydration of the phosphate groups. This correlation is sensible to the chain length, the presence of double bonds and the phase state of the lipid membrane. The presence of carbonyl groups CO modifies the profile of hydration of the two regions as observed from the comparison of DMPC and 14:0 Diether PC. The different water populations in lipid interphases would give arrangements with different free energy states that could drive the interaction of biological effectors with membranes.